Drug analysis of a fatal case of bloodstream infection combined with urinary tract infection due to echinocandin-resistant Candida glabrata - Linling Wang; Liangfen Wang; Man Liu; Yaqing Ou; Liang Yang; Rong Chen (IDCases)
When a urinary tract infection (UTI) progresses to a bloodstream infection (BSI), the choice of therapeutic drugs should consider their effectiveness against both BSI and UTI. C. glabrata exhibits strong resistance to antifungal drugs, making the treatment of BSI combined with UTI caused by this pathogen challenging. We report a fatal case of BSI combined with UTI caused by echinocandin-resistant C. glabrata in a 68-year-old female patient. The patient was treated with fluconazole, caspofungin, voriconazole, amphotericin B, and 5-flucytosine throughout the treatment process, but the infection was not controlled in the end. We analyzed the shortcomings in the medication process to provide some references for physicians in clinical treatment.